Privilege-Resistant Policies in the Middle East and North Africa : Measurement and Operational Implications - Mahmood, Syed Akhtar; Slimane, Meriem Ait Ali (Washington, DC: World Bank, 2018)
Renewing the social contract, one of the pillars of the new World Bank Group strategy for the Middle East and North Africa, requires a new development model built on greater trust; openness, transparency, inclusive and accountable service delivery; and a stronger private sector that can create jobs and opportunities for the youth of the region. Recent analytic work trying to explain weak job creation and insufficient private sector dynamism in the region point to formal and informal barriers to entry and competition. These barriers privilege a few (often unproductive) incumbents who enjoy a competition-edge due to their connections or ability to influence policy making and delivery.